How easy is it to contact the duty medical doctor responsible for acute admissions?. Issue 6751 (15th September 1990) - Bakhai, A; Goodman, F; Juchniewichz, H; Martin, A; Porter, G; White, C; Williams, L; Hopkins, A
Abstract : OBJECTIVE–To ascertain ease or difficulty of contacting duty junior doctors responsible for acute medical admissions by telephone. DESIGN–Telephone survey of hospitals in six health regions in England and Wales. SETTING–70 Randomly selected hospitals, 15 of which were excluded because of non-acceptance of acute medical admissions. PARTICIPANTS–71 Duty doctors (duty house physicians, senior house officers, or registrars responsible for acute medical admissions) in 48 hospitals; seven duty doctors in seven hospitals were excluded (four declined to participate and three required a written explanation of the survey). 67 Doctors gave full information to all questions. MAIN OUTCOME MEASURES–Time taken for hospital switchboards and duty doctors to reply to telephone call, diagnoses of patients recently admitted, and on call rotas and hours of sleep of duty doctors. RESULTS–Hospital switchboards responded within 30 seconds in 87 (74%) calls, and in 76 calls (64%) the duty doctor requested was contacted within a further two minutes. Chest pain, possibly due to myocardial infarction, was the most common reason for acute medical admissions. Nearly half (48%) of the duty doctors in larger hospitals reported having 4-5 hours sleep or less on their nights on call. Most (30) were on a one in three rota; two were on a one in two rota. CONCLUSIONS–Despite impressions to the contrary contacting the duty medical team by telephone seemed fairly easy. Although most junior doctors were on a rota of one in three or better, insufficient recognition may be given to their deprivation of sleep during nights on duty.